Highly sensitive multipoint real-time kinetic detection of Surface Plasmon bioanalytes with custom CMOS cameras - Wang, Jing; Smith, Richard J.; Light, Roger; Richens, Jo; Zhang, Jing; O'Shea, Paul; See, Chung; Somekh, Michael G. (Elsevier, 2014)
Phase sensitive Surface Plasmon Resonance (SPR) techniques are a popular means of characterizing biomolecular interactions. However, limitations due to the narrow dynamic range and difficulty in adapting the method for multi-point sensing have restricted its range of applications. This paper presents a compact phase sensitive SPR technology using a custom CMOS camera. The system is exceptionally versatile enabling one to trade dynamic range for sensitivity without altering the optical system. We present results showing sensitivity over the array of better than 10−6 Refractive Index Units (RIU) over a refractive index range of 2×10−2 RIU, with peak sensitivity of 3×10−7 RIU at the center of this range. We also explain how simply altering the settings of polarization components can give sensitivity on the order of 10−8 RIU albeit at the cost of lower dynamic range. The consistent response of the custom CMOS camera in the system also allowed us to demonstrate precise quantitative detection of two Fibrinogen antibody–protein binding sites. Moreover, we use the system to determine reaction kinetics and argue how the multipoint detection gives useful insight into the molecular binding mechanisms.